2017
DOI: 10.18632/oncotarget.18912
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA19-9 as a marker of circulating tumor cells in first reflux blood of colorectal cancer patients

Abstract: Circulating tumor cells (CTCs) are used for metastasis surveillance in cancer patients, but low detection rates limit their use in colorectal cancer (CRC). We investigated the distribution of CTCs in peripheral and portal blood of CRC patients, and analyzed the relationship between serum tumor CEA/CA19-9 markers and CTCs blood levels. CTC levels detected in first reflux/portal vein blood were higher than in peripheral blood, and liver reduced CTCs amount. CTCs-positive patients had increased serum CEA and CA 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…We found that CTC counts in CRC patients were significantly associated with both CA-125 and with TNM staging, consistent with prior findings [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that CTC counts in CRC patients were significantly associated with both CA-125 and with TNM staging, consistent with prior findings [11].…”
Section: Discussionsupporting
confidence: 91%
“…CTC detection has previously been used to evaluate patients with breast, prostate, thyroid, renal, and colon cancers [8][9][10]. While CTCs have clear relevance to disease status in individual patients, prior work suggests that only 28.6% of CRC patients exhibits a detectable CTC burden (>1 per 7.5 ml of blood) among Chinese and Western populations [11]. In addition, there is evidence that CTCs are undetectable in the peripheral blood (PB) of patients with stage I-II CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the convenience of testing, preoperative detection and low cost, more and more attention has been paid to blood markers for colorectal cancer in recent years. 13, 40-42 There have been a great number of previous studies on RDW in colorectal cancers, however, their conclusions are more inclined to the role of RDW in early cancer screening or independent effect in prognosis. In our current study, it had been found that the combined evaluation of RDW and tumor marker CEA was a more significant warning factor of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for its independent prognostic value might be credited to TMs' unique diagnostic advantages. In measuring residual tumor burden, not only TMs can reflect viable tumor mass, but it may indicate the amount of circulating tumor cells which can further forecast metastases [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%